TSS ASSIMILATION CAPACITY IN THE MAMUJU RIVER ESTUARY - Noor, Rahmat Januar; Lanuru, Mahatma; Faizal, Ahmad; ., Fathuddin (Faculty of Fisheries and Marine Science, Brawijaya University, Malang, Indonesia, 2020)
The Mamuju River Estuary is an estuary whose role is to protect coastal ecosystems (mangroves, seagrasses, coral reefs) from the negative effects of intensification of land clearing upstream and coastal. Land clearing for various human needs encourages erosion resulting in high TSS (Total Suspended Solid) concentrations in river water bodies. This study aimed to determine the assimilation capacity of the Mamuju River estuary on TSS pollutants. The results showed that TSS concentrations still met the quality standard for marine biota (mangroves: <80 mg / l) with a lower distribution pattern when getting further away from the river mouth. The flushing time at the study site is 5.6 days so the river and seawater exchange is Â± 65 times per year. The pollutant load was 586.11 tons/month. The value of the assimilation capacity reaches 255.57 tons/month. Based on these results it can be concluded that the Mamuju River estuary has experienced an overload of sediment.